Simultaneously Achieved High Open‐Circuit Voltage and Efficient Charge Generation by Fine‐Tuning Charge‐Transfer Driving Force in Nonfullerene Polymer Solar Cells. (7th December 2017) - Tang, Ailing; Xiao, Bo; Wang, Yuming; Gao, Feng; Tajima, Keisuke; Bin, Haijun; Zhang, Zhi‐Guo; Li, Yongfang; Wei, Zhixiang; Zhou, Erjun
Abstract: To maximize the short‐circuit current density ( J SC ) and the open circuit voltage ( V OC ) simultaneously is a highly important but challenging issue in organic solar cells (OSCs). In this study, a benzotriazole‐based p‐type polymer (J61) and three benzotriazole‐based nonfullerene small molecule acceptors (BTA1‐3) are chosen to investigate the energetic driving force for the efficient charge transfer. The lowest unoccupied molecular orbital (LUMO) energy levels of small molecule acceptors can be fine‐tuned by modifying the end‐capping units, leading to high V OC (1.15–1.30 V) of OSCs. Particularly, the LUMO energy level of BTA3 satisfies the criteria for efficient charge generation, which results in a high V OC of 1.15 V, nearly 65% external quantum efficiency, and a high power conversion efficiency (PCE) of 8.25%. This is one of the highest V OC in the high‐performance OSCs reported to date. The results imply that it is promising to achieve both high J SC and V OC to realize high PCE with the carefully designed nonfullerene acceptors. Abstract : The existence of the driving force in organic solar cells (OSCs) often creates a problematic trade‐off between the open‐circuit voltage and short‐circuit current. Here, fine‐tuning driving force by gradually decreasing the acceptor energy level has afforded high open‐circuit voltage (>1.15 V) and efficient charge generation (>60%) at the same time, which is instructive to the development of more efficient OSCs.